Estrategias de evaluación “Evaluó Innovando” en el aprendizaje de la biología en los estudiantes de segundo año de bachillerato general unificado paralelos “A” y “B” de la unidad educativa isabel de godín de la ciudad de riobamba, período junio - noviembre 2016. - Yumisaca Pala, Yolanda Isabel (2017)
The research was developed at Unidad Educativa Isabel de Godín in Riobamba, with the High School students of second year unified general, where there is evidences of poor performance in Biology subject, their, average grade 6.68 next to achieve the required learning, due to the application of traditional assessment techniques, which do not really test the way in which the students are learning, focusing more on the product than the process. Therefore, the objective of the present research is: “Demostrate how the use of the assessment strategies “Evaluó Innovando" improves the Biology learning”, using a structured guide with active didactic techniques and playful methodologies that promote the interest of students by knowledge, participatory and interactive learning, valuing them using tables of specifications that allow us to reflect on what the student is able to do, without forgetting that the assessment sets out the learning results, expressed in terms of acquired knowledge, developed skills and abilities. Nodaway in Ecuador this is known as formative assessment. This work was based on theoretical processes related to the topic; the methodology was considered non-experimental design, as well as scientific, deductive and inductive methods that analyze general and particular facts. The sample consisted of 61 students and 5 teachers. The hypothesis was proved using the statics technique of Z of proportions. Based on the obtained results, it was concluded that let evidences how do the proposed activities improve the learning of Biology by 66% in comparison to a 44% of initial performance. For this reason, the use of the guide of assessment strategies "Evaluó Innovando" is recommended to strengthen the learning of this subject since it promotes the interest of students for knowledge and encourage participative and interactive learning.